Microlavage: a technique for determining the volume of epithelial lining fluid. Issue 9 (September 1991) - Baldwin, D R; Wise, R; Andrews, J M; Honeybourne, D
Abstract : A new technique ("microlavage") was used to determine the volume of epithelial lining fluid recovered by bronchoalveolar lavage. A standard bronchial brush tube is used to lavage a peripheral lung subsegment rapidly with 20 ml of normal saline and the concentrations of urea and total protein are measured in the aspirated fluid. Using a very short dwell time for fluid (less than 20 seconds), this technique allows the urea dilution method to be used to quantify the epithelial lining fluid protein concentration, which is then used as an endogenous marker of the epithelial lining fluid in conventional bronchoalveolar lavage fluid. The reproducibility of the calculation of the concentration of the lining fluid protein was assessed in 10 patients by performing the method in three separate lung subsegments. The mean coefficient of variation of the urea to protein ratio was 9.0%. A comparison of microlavage and conventional lavage was made in a further 28 patients. The differential cell counts were similar by the two methods, suggesting that similar epithelial lining fluid was sampled. The application of the microlavage technique to the calculation of epithelial lining fluid volume gave a lower value than the urea dilution method in association with conventional lavage. Microlavage should provide more accurate quantification of epithelial lining fluid volume and could be used in conjunction with conventional lavage, which is still required for an adequate harvest of alveolar cells.